Risk of hearing loss in small for gestational age neonates - Melani Rakhmi Mantu; Lelani Reniarti; Sjarif Hidajat Effendi (Paediatrica Indonesiana, 2011)
Background Small for gestational age (SGA) neonates often have intrauterine growth restriction due to placental insufficiency and chronic hypoxia. These conditions may cause developmental impairment, psychosocial disabilities, or metabolic dysfunction in later life. Previous studies have shown greater incidence of speech and language disabilities, learning impairment, and neuromotor dysfunction in term SGA infants compared to term appropriate for gestational age (AGA) infants.Objective To compare hearing loss in SGA and AGA neonates using otoocoustic emission (OAE) tests and to study correlations between maternal risk factors and hearing loss in SGA neonates.Methods A cross-sectional study was performed in St. Borromeus Hospital, Limijati Hospital, and Melinda Hospital in Bandung from February to May 2010. Study subjects consisted of full-term neonates born in these three hospitals. A retrospective medical record review was performed for this study. Statistical analysis was done by multivariable logistic-regression.Results There was a total of 4279 subjects in our study, including 100 SGA neonates and 4179 AGA neonates. We observed a greater percentage of OAE 'refer' (indicating abnormal OAE) results in the SGA group compared to the AGA group (P<0.001, Z=13.247). For suhjects with OAE 'refer' results, we also analyzed the correlation to the following maternal risk factors: smoking, hypertension, diabetes mellitus and asthma. We also found significant differences betweenÂ  those with and without each of the four maternal risk factors studied (P< 0.001). By using multivariant analysis to compare SGA and AGA neonates, we found the odds ratio (OR) to he 4.34 (95% CI 2.52 to 7.49, P=0.001), meaning the SGA group had a 4.34 times higher risk of hearing loss than the AGA group.Conclusion SGA neonates had a higher risk of hearing loss than AGA neonates. In addition, maternal smoking, hypertension, diabetes mellitus and asthma significantly correlated to hearing loss in all newborns. [